ICTV Virus Taxonomy Profile: Paramyxoviridae. (14th October 2019) - Rima, Bert; Balkema-Buschmann, Anne; Dundon, William G.; Duprex, Paul; Easton, Andrew; Fouchier, Ron; Kurath, Gael; Lamb, Robert; Lee, Benhur; Rota, Paul; Wang, Linfa; ,
Abstract : The family Paramyxoviridae consists of large enveloped RNA viruses infecting mammals, birds, reptiles and fish. Many paramyxoviruses are host-specific and several, such as measles virus, mumps virus, Nipah virus, Hendra virus and several parainfluenza viruses, are pathogenic for humans. The transmission of paramyxoviruses is horizontal, mainly through airborne routes; no vectors are known. This is a summary of the current International Committee on Taxonomy of Viruses (ICTV) Report on the family Paramyxoviridae . which is available at ictv.global/report/paramyxoviridae .